2017
DOI: 10.1158/2159-8290.cd-16-0844
|View full text |Cite
|
Sign up to set email alerts
|

OTX2 Activity at Distal Regulatory Elements Shapes the Chromatin Landscape of Group 3 Medulloblastoma

Abstract: Medulloblastoma is the most frequent malignant pediatric brain tumor and is divided into at least four subgroups known as Wnt, SHH, Group 3 and Group 4. Here we characterized gene regulation mechanisms in the most aggressive subtype, Group 3 tumors, through genome-wide chromatin and expression profiling. Our results show that most active distal sites in these tumors are occupied by the transcription factor OTX2. Highly active OTX2 bound enhancers are often arranged as clusters of adjacent peaks and are also bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 57 publications
1
53
0
Order By: Relevance
“…Indeed, NEUROD1 and NR2F1 were both significantly upregulated following OTX2 KD in our MB tumorspheres (Table ). In addition, OTX2 is associated with regulation of histone modifications (Bunt et al ., ) and has recently been found to cooperatively control the active enhancer landscape in Group 3 MB (Boulay et al ., ). Therefore, OTX2 may colocalize with specific histone modifications (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, NEUROD1 and NR2F1 were both significantly upregulated following OTX2 KD in our MB tumorspheres (Table ). In addition, OTX2 is associated with regulation of histone modifications (Bunt et al ., ) and has recently been found to cooperatively control the active enhancer landscape in Group 3 MB (Boulay et al ., ). Therefore, OTX2 may colocalize with specific histone modifications (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…5a-d). Furthermore, analyzing the dataset of ATACseq analysis [22] of human ESCs (GSM2433022) [23] and human somatic cells (GSM1939273) revealed that the chromatin structure around the TERT-DMR was "open" in TERT-expressing pluripotent cells, but was closed in somatic cells. These data indicated that histones at the TERT-DMR were active state, even though the DNA was highly methylated in human iPSCs.…”
Section: Methylated Tert-dmr Maintained Open Chromatinmentioning
confidence: 99%
“…TFs and chromatin remodelers are key regulators of the nucleosome occupancy and positioning.Given that chromatin remodelers lack sequence specificity, sequence-specific TFs are proposed to play central roles in establishing the differential accessibility of Otx2 CRMs.It is not known whether the TFs that initiate remodeling of chromatin accessibility are the same TFs that activate CRMs. Otx2 and Sox2, which can activate the O5 and O9 CRMs in the retina, can function as pioneer factors and regulate chromatin remodeling in other systems (Iwafuchi-Doi and Zaret 2014;Boulay et al 2017). Crx can regulate the chromatin remodeling of genes associated with photoreceptor differentiation(Ruzycki et al 2018).…”
mentioning
confidence: 99%